2015
DOI: 10.1111/iej.12477
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an artefact reduction algorithm in the diagnosis of in vitro vertical root fracture in four different root filling conditions on CBCT images

Abstract: The application of the ARA did not influence the diagnosis of root fractures, and its effects did not depend on root conditions. In relation to the filling materials, gold posts reduced the overall CBCT diagnostic ability, regardless of the use of the ARA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 36 publications
(83 reference statements)
3
38
0
1
Order By: Relevance
“…Pinto et al Effect of parameters on fracture detection International Endodontic Journal, 50, 586-594, 2017 which may impair CBCT diagnostic performance, making the diagnosis more difficult and time-consuming (Costa et al 2011, Moudi et al 2014, Bezerra et al 2015, Ferreira et al 2015. In the present study, the diagnosis of VRF was compromised by the presence of metallic posts and gutta-percha, in accordance with previous studies (Costa et al 2011, Wang et al 2011, Khedmat et al 2012, Junqueira et al 2013, Patel et al 2013, Neves et al 2014, Ferreira et al 2015, de Rezende Barbosa et al 2016). On the contrary, it has also been reported that the presence of gutta-percha root fillings does not decrease the accuracy of VRF diagnosis (Hassan et al 2009, Melo et al 2010, Moudi et al 2014.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Pinto et al Effect of parameters on fracture detection International Endodontic Journal, 50, 586-594, 2017 which may impair CBCT diagnostic performance, making the diagnosis more difficult and time-consuming (Costa et al 2011, Moudi et al 2014, Bezerra et al 2015, Ferreira et al 2015. In the present study, the diagnosis of VRF was compromised by the presence of metallic posts and gutta-percha, in accordance with previous studies (Costa et al 2011, Wang et al 2011, Khedmat et al 2012, Junqueira et al 2013, Patel et al 2013, Neves et al 2014, Ferreira et al 2015, de Rezende Barbosa et al 2016). On the contrary, it has also been reported that the presence of gutta-percha root fillings does not decrease the accuracy of VRF diagnosis (Hassan et al 2009, Melo et al 2010, Moudi et al 2014.…”
Section: Discussionsupporting
confidence: 85%
“…, de Rezende Barbosa et al . ). On the contrary, it has also been reported that the presence of gutta‐percha root fillings does not decrease the accuracy of VRF diagnosis (Hassan et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations